Heat Shock Protein 70 Upregulation by Geldanamycin Reduces Brain Injury in a Mouse Model of Intracerebral Hemorrhage - Manaenko, Anatol (2010)
This study investigated the effect of geldanamycin post-treatment on the development of secondary brain injury and neurological deficits in a mouse model of intracerebral hemorrhage. CD-1 mice received stereotactic injection of collagenase type VII into the right basal ganglia. Treatment groups were administered 1mg/kg (low dose) or 10mg/kg (high dose) of geldanamycin. Mice were euthanized at two time-points: 24 hrs or 72 hrs. Blood-brain-barrier permeability, brain edema, and neurobehavioral deficits were assessed. Additionally, the effects of geldanamycin on heat shock protein 27 and 72; tumor necrosis factor-alpha and interleukin 1 beta expressions were evaluated. High dose geldanamycin significantly attenuated blood brain barrier disruption and brain edema after intracerebral hemorrhage. Neurobehavioral outcomes were significantly improved in some parameters by high dose treatment. Molecular results showed a marked increase in heat shock protein 72 expression in ipsilateral brain of geldanamycin treated groups with a reduction in the pro-inflammatory tumor necrosis factor-alpha. CONCLUSION: Geldanamycin post-treatment is neuroprotective in the mouse model of intracerebral hemorrhage. Geldanamycin administration results in reduction of inflammation, preservation of blood-brain-barrier and amelioration of neurobehavioral deficits after an insult possibly by upregulation of heat shock protein 72.